Alternations between physical and cognitive tasks in repetitive work – effect of cognitive task difficulty on fatigue development in women. Issue 8 (3rd August 2019) - Mixter, Susanna; Mathiassen, Svend Erik; Hallman, David
Abstract: In a context of job rotation, this study determined the extent to which the difficulty of a cognitive task (CT) interspersed between bouts of repetitive, low-intensity work (pipetting) influences recovery from fatigue. Fifteen participants performed three experimental sessions, each comprising 10 repeats of a 7 min + 3 min combination of pipetting and CT. The CT was easy, moderate or hard. Surface electromyography (EMG amplitude of the forearm extensor and trapezius muscles) and self-reports was used to assess fatigability. Perceived fatigue and trapezius EMG amplitude increased during sessions. CT difficulty influenced fatigue development only little, besides forearm extensor EMG increasing more in CT3 than in CT1 and CT2. During CT bouts, fatigability recovered, and to a similar extent irrespective of CT. Thus, CT difficulty influenced recovery of perceived as well as performance fatigability to a minor extent, and may not be a critical issue in job rotation comprising alternating physical and cognitive tasks. Practitioner summary: Alternations between physical and cognitive tasks may be an attractive option for job rotation. In this study on women, we show that the difficulty of the cognitive task influences recovery from fatigue only little and we conclude that cognitive difficulty, within reasonable limits, may be a minor issue in job rotation.